Bridging Continents in Teaching Environmental History: Rio de Janeiro and Vienna - Oliveira, Rogério Ribeiro de; Schmid, Martin (Historia Ambiental Latinoamericana y Caribeña (HALAC) revista de la Solcha, 2011)
This paper presents and critically discusses an experiment in environmental history didactics. For the first time - as far as we know - an intercontinental course in environmental history was designed and offered, simultaneously in Vienna (Austria) and Rio de Janeiro (Brazil). From an environmental history perspective a city is a socio-natural site, its present shape is the result of a co-evolutionary process of nature and society. This paper is a teacher’s reflection about the potentials and limitations of e-learning and blended learning (the combination of face-to-face and virtual communication) based teaching of urban environmental history in an intercontinental, multilingual and intercultural setting.